2020
DOI: 10.3390/ijms21062082
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Responsible for the Anticoagulant Properties of Neurotoxic Dendroaspis Venoms: A Viscoelastic Analysis

Abstract: Using thrombelastography to gain mechanistic insights, recent investigations have identified enzymes and compounds in Naja and Crotalus species' neurotoxic venoms that are anticoagulant in nature. The neurotoxic venoms of the four extant species of Dendroaspis (the Black and green mambas) were noted to be anticoagulant in nature in human blood, but the mechanisms underlying these observations have never been explored. The venom proteomes of these venoms are unique, primarily composed of three finger toxins (3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…This laboratory became aware of this work recently, and using a similar approach, demonstrated an identical outcome wherein the anticoagulant activity of the purified phospholipase A 2 (PLA 2 ) of Apis mellifera venom was inhibited by CORM-2 in a CO-independent, albumin-inhibitable fashion [15]. Furthermore, we recently demonstrated that the anticoagulant metalloproteinases of mamba venoms are inhibited by CORM-2 in a CO-independent, albumin-inhibitable manner [16]. Taken as a whole, it was entirely possible that Ru-based interactions with venom proteins could be responsible for the inhibition noted in our previous works [13]; and critically, if Ru-based modifications were the underpinning of such inhibition rather than the interaction of CO with a heme group, then Ru-based CORMs could well serve as permeant antivenom agents.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…This laboratory became aware of this work recently, and using a similar approach, demonstrated an identical outcome wherein the anticoagulant activity of the purified phospholipase A 2 (PLA 2 ) of Apis mellifera venom was inhibited by CORM-2 in a CO-independent, albumin-inhibitable fashion [15]. Furthermore, we recently demonstrated that the anticoagulant metalloproteinases of mamba venoms are inhibited by CORM-2 in a CO-independent, albumin-inhibitable manner [16]. Taken as a whole, it was entirely possible that Ru-based interactions with venom proteins could be responsible for the inhibition noted in our previous works [13]; and critically, if Ru-based modifications were the underpinning of such inhibition rather than the interaction of CO with a heme group, then Ru-based CORMs could well serve as permeant antivenom agents.…”
Section: Introductionmentioning
confidence: 85%
“…Similarly, increased RuCl3 concentrations significantly decrease TMRTG and increase MRTG values when PBS is the vehicle. However, and critically, the coagulation kinetic differences caused by RuCl3 are significantly enhanced by the fluid it is dissolved in as indicated by the two-way ANOVA significance values in each panel of As all of the venoms investigated over the past few years have been suspended in PBS for the purposes of preserving enzymatic function within a physiological pH, storage, and experimentation [1][2][3][4][5][6][7][8][9][10][11][12][13]15,16], it seemed prudent to continue with the use of PBS in the subsequently described experimental series assessing the effects of RuCl3 on the three venoms of the present work. The caveat that should be kept in mind was that small enhancements of MRTG in human plasma could be secondary to a RuCl3/PBS interaction when determining if RuCl3 inhibited venom procoagulant activity.…”
Section: Assessment Of the Effects Of Rucl3 On Human Plasmatic Coagulmentioning
confidence: 99%
See 3 more Smart Citations